Essentials of Research Design and Methodology - Geoffray Marczyk, David Dematteo (John Wiley & Sons, Inc, 2005)
Although research studies are conducted in many diverse fields of science, the general goals and defining characteristics of research are typically the same across disciplines. For example, across all types of science, research is frequently used for describing a thing or event, discovering the relationship between phenomena, or making predictions about future events. In short, research can be used for the purposes of description, explanation, and prediction, all of which make important and valuable contributions to the expansion of what we know and how we live our lives. In addition to sharing similar broad goals, scientific research in virtually all fields of study shares certain defining characteristics, including testing hypotheses, careful observation and measurement, systematic evaluation of data, and drawing valid conclusions. One INTRODUCTION AND OVERVIEW TEAM LinG - Live, Informat